Stunting prevention through increasing community participation during the Covid-19 pandemic in Guwosari Village, Pajangan, Bantul - Wiwik Kusumawati; Alfaina Wahyuni; Nur Hayati (Community Empowerment, 2023)
Stunting is a condition of toddlers who have less length or height compared to their age. The toddlers' stunting case in Pajangan District is the highest in Bantul and the handling has not shown satisfactory results. The causes of stunting that have been identified by the Bantul District Health Office, the majority occur due to the economic condition of poor families. This factor accounts for 47.29% in cases of stunting, followed by poor parenting and low awareness of exclusive breastfeeding culture. The existence of the Covid-19 pandemic has also affected the incidence of stunting. This community service aims to increase knowledge and skills as well as increase community participation in preventing stunting. Community service activities are carried out using lecture methods and direct discussions with mothers in Guwosari Village, Pajangan, Bantul. The activity was preceded by a pretest and ended by a posttest. Based on the evaluation results, it showed an increase in stunting knowledge with an average pretest of 11.9% and a posttest of 13.4%. So it can be concluded that there was an increase of 1.4% in stunting knowledge after program.